Etna Bulk rock (major and trace elements) analyses 2022 (BRET_2022) - Miraglia, Lucia (Istituto Nazionale di Geofisica e Vulcanologia (INGV), 2022)
The database consist of Bulk rock compositions (major and trace elements) of lava and pyroclasts sampled at Etna during the 2022 INGV-OE petrologic monitoring activity.

Il database contiene le composizioni delle rocce totali (elementi maggiori ed in tracce) di lave e piroclastiti campionati all'Etna nel 2022 durante l’attività di monitoraggio petrologico dell’INGV-OE.
Analisi degli elementi maggiori e in tracce delle rocce totali dei prodotti emessi dall'Etna nel 2022
BRET_2022
The preparation and analyses of the sample have been performed at INGV laboratories.
After archiving, the samples were reduced to powder, the LOI was determined and finally they were melted (Miraglia, 2012 ). The beads were analyzed for X-ray fluorescence.
The bulk rock compositions have been analyzed at INGV-OE with the Rigaku Primus II XRF.
The accuracy of our measurements has been checked through replicate analyses of the international standard (Jarosewich et al., 1980). The precision, expressed as relative standard deviation, is less than 1% for SiO2, Al2O3, FeO, MgO and CaO and less than 3% for TiO2, MnO, Na2O, K2O and P2O5 (Miraglia, 2013), <5% for Ba, Ce, La, Nb, Nd, Rb, Sm, Sr, V, Y, Yb, Zn e Zr, e <10% for Cr, Ni e Th (Miraglia, 2017). Each measure is the average of 3 analyses.
Dataset legend
Sample Label: name identificative of the sample,
Date of sample's eruption: (DD/MM/YYYY);
Eruptive vent/Fissure: the Acronyms used for Etna summit craters are VOR= Voragine Crater, BN=Bocca Nuova Crater, NEC=North-East Crater, SEC=South-East Crater, NSEC=New South-East Crater;
Activity type: description of the eruption activity (eg: effusive, spattering, Strombolian explosions, paroxysm, ash emission, other)
Sample type/size: lava, bomb or lapilli).
More details about the samples are available in the Access Archive of the INGV-OE Petroteca.
Keywords: Etna; XRF; Bulk rock analyses; Major elements; Trace elements; Petrological monitoring